Spatial Management to Enhance Tourism Industrial Ecology and Natural Resources Conservation: A Case Study of Kakas Sub-district, Lake Tondano, North Sulawesi - Wowiling, Steiva A. S; Bisri, Mohammad; Husain, Jailani; Hakim, Luchman (Asian Journal of Agriculture and Rural Development, 2013)
Lakes throughout the world recently are facing serious problem which lead to its extinction. Integrating conservation and tourism in lakes and it surrounding area offer new opportunities for environment, development and economic growth in harmony. The aim of the research is to identify spatial composition of an area adjacent to Lake Tondano as a basic model of tourism industrial ecology. The study was set up at Kakas as one of the villages which is located adjacent to Lake Tondano. The result of the study shows that the model area adjacent to Lake Tondano acting as a sustainable rural destination consists of several land uses, including shrubs, paddy field, orchards, traditional plantation, and settlement with a total area of c.a. 27.80 km2. Based on its characteristic, tourism in the study site should be projected in a form of rural tourism. There are natural and cultural capitals found in the study area, and their existence principally represents the potential resources for tourism development. These potential attractions are spatially distributed in three areas, which can be linked through a triangle diamond model to meet a sustainable and competitive tourism industrial area. The opportunities of such concept also come to the existence of a corridor which is able to link each point area to become a single and integrative tourism destination. Challenges for the tourism industrial ecology in Kakas, however, lie on its ability to optimize resources, while at the same time minimize potential negative impacts to the environment, especially Lake Tondano.